The effect of vinasse as a carbon source on the activity of urease-producing bacteria in the microbially induced calcite precipitation (MICP) approach. - Negin Pirhadi; Habib Nadian; B. Khalilimoghadam; Hossein Motamedi (Desert)
One of the most important causes of soil desertification is wind erosion. Deserts are known for their poor physical, chemical, and biological properties. In order to solve the problem of loose sand, many solutions have been thought and used so far. Today, scientists have greatly benefited from the capabilities of MICP in the field of sand dune stabilization, which seems to be an environmentally friendly solution. In Khuzestan, a lot of "vinasse" enter the environment every year, which is considered a pollutant. Combining it with beneficial native microorganisms can turn it into a valuable ingredient. The objectives of this study were to investigate the microbial activity of bacteria isolated from the sand dunes of Khuzestan in Iran using vinasse as a carbon source for growth. In order to eliminate the effect of competition and investigate the activity of the studied bacterial isolates (Bacillus licheniformis MZ057843, MZ057842, OP329211, and Sporosarcina pasteurii), the samples of sand dunes collected from Khuzestan were first sterilized. Then, inoculated vinasses were added to them, and the prepared samples were incubated for five weeks. The experiments (counting bacteria by plate count technique, Soil catalase by the method of titration with KMnO4, and Soil microbial respiration by measuring the amount of CO2) were measured after the first, third and fifth weeks of incubation time. Then, the data were analyzed by split plot in time design. The current study showed significant effects of vinasse, bacteria, time and their interaction in all three tests (p < 0.0001). Isolate B1 was able to cause the highest amount of microbial population and microbial respiration, and isolate B3 produced the highest amount of catalase enzyme in the soil. Among the three types of vinasse, V3 had the highest amount of catalase and microbial population, and V2 had the highest soil microbial respiration rate. The best incubation time for the microbial respiration and population tests was the first week, and third week of incubation for the catalase test. Generally, native Bacillus bacteria grew in vinasse as a carbon source and perhaps the potential of vinasse as a mulch can be explored. However, more research is needed to use it in soil stabilization operations.